Intelligent Control and Computer Engineering - Ao, Sio-Iong.; Castillo, Oscar; Huang, Xu.; SpringerLink (Online service) (2011)
A large international conference on Advances in Intelligent Control and Computer Engineering was held in Hong Kong, March 17-19, 2010, under the auspices of the International MultiConference of Engineers and Computer Scientists (IMECS 2010). The IMECS is organized by the International Association of Engineers (IAENG). Intelligent Control and Computer Engineering contains 25 revised and extended research articles written by prominent researchers participating in the conference. Topics covered include artificial intelligence, control engineering, decision supporting systems, automated planning, automation systems, systems identification, modelling and simulation, communication systems, signal processing, and industrial applications. Intelligent Control and Computer Engineering offers the state of the art of tremendous advances in intelligent control and computer engineering and also serves as an excellent reference text for researchers and graduate students, working on intelligent control and computer engineering.
Artificial intelligence -- Control engineering -- Decision supporting systems -- Automated planning -- Automation systems -- Systems identification -- Modelling and simulation -- Communication systems -- Signal processing -- Industrial applications.
Keywords: Engineering; Artificial intelligence; Artificial Intelligence (incl. Robotics).; MECHATRONICS; CONTROL, ROBOTICS, MECHATRONICS